2004
DOI: 10.1364/opex.12.002762
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical demonstration of validity and limitations in fringe-resolved autocorrelation measurements for pulses of few optical cycles

Abstract: Using 3.6-and 5.3-fs pulses, we demonstrated theoretically and experimentally that fringe-resolved autocorrelation (FRAC) traces are distorted by bandwidth limitations of the second-harmonic generation (SHG) in 10-µm-thick, type I β -BaB 2 O 4 for pulses shorter than sub-5 fs. In addition, detailed numerical analysis of the SHG showed that the optimum crystal angle where the FRAC trace distortion becomes minimum is in disagreement not only with the phase-matching angle but also with the angle where the FRAC si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…One approach to obtain the shortest pulse is to optimize the second harmonic signal by focusing the compressed white-light pulses to a nonlinear crystal. However, it was found that by optimizing the SH signal, neither genetic algorithm nor evolutionary algorithm can compress the pulse with high accuracy [19,20]. Another approach is to measure the spectral phase of the white light from the fiber and feed the measured value to the phase modulator for correction.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…One approach to obtain the shortest pulse is to optimize the second harmonic signal by focusing the compressed white-light pulses to a nonlinear crystal. However, it was found that by optimizing the SH signal, neither genetic algorithm nor evolutionary algorithm can compress the pulse with high accuracy [19,20]. Another approach is to measure the spectral phase of the white light from the fiber and feed the measured value to the phase modulator for correction.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Such nonlinear chirp is not compensated for by conventional passive dispersion elements (for example, a grating pair, a prism pair, chirped mirrors, and their combinations) because of interrelation between second-order and higher order phase dispersions of their compensators and their bandwidth limitations. In addition, few-to mono-cycle pulses generated as a result of pulse compression cannot be characterized correctly by a conventional technique of fringe resolved autocorrelation (FRAC) owing to the so called filter effect in second-harmonic generation (SHG) processes [1]. Manuscript In recent years, high-powered pulse compression to few cycles was reported using a gas-filled hollow fiber, chirped mirrors, and an SHG frequency-resolved optical gating (SHG-FROG) measurement [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the time required to run the chirp compensation experiment for the generation of 11-fs pulses after about 1000 iterations was roughly 15 min. In addition, for shorter pulse compression in the near-octave bandwidth and few-cycle region, the SHG intensity cannot be the unique target and cannot always define a minimized pulse [1]. Fig.…”
Section: Introductionmentioning
confidence: 99%